Improvement of Exposition Text Writing Motivation and Skills Through the Application of the Problem Based Learning Model - Martanti Dwi Kristyanawati; Sarwiji Surwandi; Muhammad Rohmadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study aims is to improve: (1) student learning motivation; and (2) students' writing skills in writing exposition texts of class VIII on State of Junior High School 3 Surakarta through the application of the Problem Based Learning model. This type of research is Class Action Research (CAR). This research was conducted in three cycles. This research was conducted in State of Junior High School 3 Surakarta in the first semester of the 2018/2019 academic year. This research was conducted in five months, starting from July to November 2018. The subjects of this study were students of class VIII- 9 in the first semester of the 2018/2019 academic year with a total of 32 students. The method of data collection is done by using tests, observations, questionnaires and document techniques. Data analysis techniques are carried out using critical analysis. Based on the analysis, the study concluded that: (1) the application of the Problem Based Learning model was able to increase students' motivation in learning Indonesian. This is indicated by an increase in the average score of learning motivation and the number of students with a learning motivation score of classification A (Very Good) and B (Good) in each cycle performed; and (2) the application of the Problem Based Learning model is able to improve students' writing skills in writing exposition texts of class VIII SMP Negeri 3 Surakarta in the first semester of the academic year 2018/2019. This is indicated by an increase in the average student score and the level of student mastery throughout the cycle. The average score of students' writing skills in exposition text writing, increased from 63.09 in the initial conditions, increased to 73.00 at the end of the first cycle, increased to 76.78 at the end of the second cycle, and then increased to 80.22 at the end from Cycle III. The level of mastery of student learning increased from 12.50% in the initial conditions, increasing to 43.75% at the end of the first cycle, increasing to 68.75% at the end of the second cycle, then increasing to 100.00% at the end of cycle III.